2017
DOI: 10.1007/s00267-017-0904-6
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Willingness to Adopt Conservation Agriculture: New Evidence from Lebanon

Abstract: With increasing food insecurity and climate change, conservation agriculture has emerged as a sustainable alternative to intensive conventional agriculture as a source of food supply. Yet the adoption rate of conservation agriculture is still low. Our paper analyses the factors affecting farmers' willingness to adopt conservation agriculture in Lebanon. The findings show that household characteristics-years of farming and farm size affect conservation agriculture adoption. However, household characteristics al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 49 publications
2
15
0
6
Order By: Relevance
“…Only 18 cooperative members of the almost 700 in total were less than 30 years of age whereas almost 60% of all members were over 40. Similar concerns of an aging farming population and decreasing participation of youth in the agro-food sector were also recently voiced by others as Chalak (et al 2017) and ILO (2018). Comparable figures to those of ILO (2018) are also recorded by this study showing only 27% of members aged between 30 and 40.…”
Section: Resultsmentioning
confidence: 53%
“…Only 18 cooperative members of the almost 700 in total were less than 30 years of age whereas almost 60% of all members were over 40. Similar concerns of an aging farming population and decreasing participation of youth in the agro-food sector were also recently voiced by others as Chalak (et al 2017) and ILO (2018). Comparable figures to those of ILO (2018) are also recorded by this study showing only 27% of members aged between 30 and 40.…”
Section: Resultsmentioning
confidence: 53%
“…In general, although the worldwide adoption of NT is increasing, Chalak et al . () showed that the willingness of wheat farming households to adopt conservation agriculture (including NT) in arid and semiarid regions of Middle East is still limited and restricted by several factors. They listed the key determinants of conservation agriculture adoption as farming experience, information sources, frequency of irrigation, severity of weed infestation in the past, participation in specific training, and farmer perception about the long‐term impact of the conservation agriculture.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Bekaa Valley has been a focus of research by many local and regional institutions such as the Lebanese Agricultural Research Institute (LARI), the International Center for Agricultural Research in the Dry Areas (ICARDA), and the American University of Beirut (AUB). For example, AUB has been testing the ecological and yield impacts of conservation agriculture in the Bekaa valley (Chalak et al, 2017 ). Such interventions should have raised awareness of the importance of environmentally sustainable agriculture practices.…”
Section: Discussionmentioning
confidence: 99%